Ecological building material in glass, sand and polyplastics (vapoli) - Rocha Alvarez, Delma Esther; Pérez, Carol; Villanueva, Jorge (Ecomaterials, 2023)
Abstract: This article refers to the development of a new environmentally friendly construction material; it mentions concepts of contamination in Colombia where the lack of reuse of recyclable materials is demonstrated with figures, and states its objectives and justification according to the needs or deficiencies outlined in the document. In the research, studies of similar models are carried out where research related to the proposed topic is shown; likewise, articles and national and international laws that support this work are evoked.